Characteristics of initial symptoms in patients with dementia with Lewy body disease - Fei, Min; Wang, Fei; Wu, Hao; Liu, Shuai; Gan, Jinghuan; Ji, Yong (Frontiers in Neurology, 2022)
Background Dementia with Lewy bodies (DLB) is the second most common neurodegenerative dementia. Although DLB is characterized by fluctuating cognitive impairment, some symptoms may appear before cognitive impairment, including rapid eye movement, sleep behavior disorder (RBD), psychiatric symptoms, autonomic symptoms, Parkinson's symptoms, etc. Therefore, DLB may be misdiagnosed as other diseases in its early stage. Objective This study aimed to investigate the characteristics of initial symptoms of DLB, which could potentially offer essential clues for the earliest diagnosis of this disorder. Methods A total of 239 patients with probable DLB who visited the cognitive impairment outpatient department of Tianjin Huanhu Hospital from September 2015 to March 2021 were consecutively enrolled. We retrospectively evaluated the initial symptoms of all included participants. The time of onset of initial symptoms was also assessed. Results The most frequent initial symptom was memory loss (53.9%), followed by psychiatric symptoms (34.7%), RBD (20.9%), parkinsonism (15.1%), and autonomic symptoms (10.1%). Significant gender and age differences existed in the initial symptoms of patients with DLB. Conclusions Our study elucidated the initial symptoms in patients with probable DLB. RBD was significantly more reported by men than by women, whereas women showed a higher incidence of visual and auditory hallucinations. A better understanding of the initial symptoms of DLB could lead to a more accurate diagnosis.